PEDAGOGICAL CONDITIONS OF DEVELOPMENT OF INFORMATION-COMMUNICATIVE COMPETENCE OF UNIVERSITY SCHOOL TEACHERS. (Multidisciplinary Journal of Science and Technology, 2024)
This article presents ideas about the pedagogical foundations of developing communicative competence of future teachers. The content of pedagogic subjects is directed to the development of the humanistic basis of communicative competence of students of pedagogic higher education institutions.